FAKTOR-FAKTOR YANG MEMPENGARUHI PENDUDUK LANJUT USIA MEMILIH UNTUK BEKERJA - Moch. Affandi (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2009)
This study analysis the determinant of the old generations workers (more than 60years old) to work or to enter teh labour market. Using Sakerti data, it can be seenthat they have low level of education, low level of family expenditure, are living inthe rural area and working in the informal sector. Generally, the condition of familyeconomy is the main determinant for old generation workers to work or join thelabour market. Therefore, there is a need to prepare the work conditions and activi-ties that fit for old generation workers due to the fact they are not productive any-more in term of employment.Keywords: old generation workers, labour market and informal sector